Evaluation of screening test for gestational diabetes mellitus in pregnant women without risk factor - Yasaei, fakhrolmolok; hesarashrafi, zhila (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim Diabetes mellitus affects 3-5% of all pregnancies, and because of high perinatal mortality and morbidity global screening appears logical. The aim of this study was to evaluate the screening test for gestational diabetes mellitus in pregnant women without risk factor in Taleghani Hospital, Tehran, Iran.